Avaliação da capacidade de mascaramento de diferentes agentes cimentantes e espessuras de cerâmica sobre substratos escurecidos - Righes, Danielle Zorzo (2023)
The objective of this study was to evaluate the effectiveness of different luting agents (composite resin Filtek Z350 XT, Filtek Z350 XT Flow and resin cement RelyX Veneer – 3M) and different thicknesses of Lithium Dissilicate ceramic laminates 0.5 and 1.2 mm for masking discolored substrates (A2; A3.5; C2; C3 and C4), originating two articles. Five specimens of each of the different luting agents were made with 0.1 mm thickness and 11 mm diameter. Five ceramic discs with 11 mm in diameter were made for each of the mentioned thicknesses. The color reading of the specimens was performed using a reflection spectrophotometer (SP60, EXRite) by mounting the ceramic/luting agent set on a discolored substrate after 24 hours of storage in water. The masking ability was evaluated based on the calculation of the ΔE, performed between the inherent substrate and the specimens on the discolored substrate. Comparative analyzes were also carried out between the reading of the color on the darkened substrate from the CIEDE2000 equation and analysis of the perceptibility and acceptability thresholds. The average of inter-group ΔE00 values were analyzed using analysis of variance (ANOVA) and Bonferroni's post hoc test. Statistical analysis was performed using the SPSS software (IBM Co. Armonk, NY USA), considering the statistical significance of p<0.05. It was concluded that no luting agent and the different thicknesses were able to mask discolored substrates.